A Descriptive Grammar of Hindko, Panjabi, and Saraiki - Bashir, Elena (Mouton-CASL grammar series ;, 2019)
Hindko, Panjabi, and Saraiki are three closely related, geographically contiguous languages of Pakistan. Together, they are the native language of some 125 million people. Panjabi alone ranks among the 15 most widely spoken languages in the world. The Grammar of Hindko, Panjabi, and Saraiki provides a comparative description of these three language varieties, focusing, where possible, on the variety of Hindko spoken in Abbottabad, the Panjabi spoken in Lahore, and the Saraiki spoken in Multan. Based on both fieldwork and corpus research, the grammar provides coverage of the phonology, orthography, morphology, and syntax of the language, with extensive exemplification presented in the native Perso-Arabic script along with standard Roman representations and morphological analysis. Written in an accessible style from a basic linguistic theory perspective, this work will be of use to linguistic researchers, language scholars, and students of the languages of Pakistan and South Asia.